Microstructure development of pearlitic railway steels subjected to fast heating. (September 2022) - Mattos Ferreira, V.; Mecozzi, M.G.; Petrov, R.H.; Sietsma, J.
Graphical abstract: Highlights: Comparable hardness is obtained for WEL produced in laboratory and the one from field conditions. Similar microstructural features are observed between WEL from field and after a single cycle of fast heating and quenching. Grain refinement observed in WEL produced during wheel/rail contact is not reproducible by thermal heating only. Mn homogeneization is obtained after 5 minutes soaking at high temperatures. Abstract: The influence of soaking and cooling rates on the final microstructure of a R260Mn pearlitic railway steel subjected to fast heating is investigated. Fast-heating experiments followed or not by soaking and cooling at different rates were performed using quenching dilatometry on railway steel specimens obtained from the rail head. Additional cyclic heating and quenching experiments were done to investigate the evolution of the microstructure during thermal cycling, which is relevant for railway applications. The final microstructure is characterized via microhardness measurements, optical microscopy and scanning electron microscopy. The microstructural features are distinguished and the influence of each condition is detailed. The study allows the construction of transformation diagrams during cooling after fast heating. Furthermore, comparison between the final microstructures obtained in controlled laboratory conditions and field White Etching Layers is presented. The obtained results can serve as a guideline for future reproduction of White Etching Layers in laboratory conditions and interpretation of field conditions.